Analisis Legalitas dan Kualitas Produk Air Minum Kemasan (AIDRAT) Pada CV. Aidrat Pondok Pesantren Sunan Drajat - Iffan Al Faris; Ari Dimas Afandi; Abdur Rahman (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
This research aims to examine the legality and quality of the bottled drinking water product under the AIDRAT brand. Product legality refers to compliance with applicable laws and regulatory standards, while product quality refers to the product's ability to meet consumer expectations and needs. The research employs a qualitative approach with a literature study method, which involves understanding and studying relevant theories from various literature sources. The research results show that AIDRAT beverages have met the legality requirements, such as having a distribution permit from BPOM (Indonesia's Food and Drug Administration), halal certification from LPPOM MUI (Indonesian Ulema Council's Food, Drug, and Cosmetics Study Institute), and compliance with the Indonesian National Standard (SNI). In terms of quality, AIDRAT beverages use natural mountain spring water processed with modern technology, such as reverse osmosis, to maintain purity and freshness. These beverages are also rich in oxygen and do not contain preservatives or artificial additives. The conclusion of this research is that AIDRAT bottled drinking water is a product that has met all safety and quality requirements, both in terms of legality and product quality.